Solubility of ethyl acetate in diluted aqueous solutions of fructose. (8th October 2012) - Borges, Rafael P.; Silva, Flávio C.; Franco, Moilton R.
ABSTRACT Ethyl acetate solubility data were experimentally determined in diluted solutions containing fructose. Concentrations results for the organic solute in water–fructose solution at temperatures between 278.2 and 293.2 K are new. However, it was possible to compare and discuss the solubility behaviour by regarding fructose concentrations and temperature effects. The results confirmed that the solubility of ethyl acetate decreases as the fructose concentration increases. Also, some changes could be observed in the solubility of the acetate when there were variations of temperature. Ethyl acetate demonstrated the same behaviour in solutions of fructose as is observed in pure water; the solubility decreased with the increasing temperature. Copyright © 2012 John Wiley & Sons, Ltd.